Influence of Age of Onset on Huntington's Disease Phenotype. (9th July 2020) - Kwa, Lauren; Larson, Danielle; Yeh, Chen; Bega, Danny
Background: Older patients with Huntington's disease (HD) are often thought to have a slower progressing disease course with less behavioral symptoms than younger patients. However, phenotypic differences based on age of onset have not been well characterized in a large HD population. This study will determine the difference in manifestations and disease progression between patients with young, typical, and late onset adult HD at different stages of disease. Methods: Data obtained from Enroll-HD. Adults with manifest HD were included. Age groups were defined as young onset (YO: 20-29 years), typical onset (TO: 30–59 years), and late onset (LO: 60+ years). Subjects were categorized by TFC score, from Stage I (least severe) to Stage V (most severe). Motor, cognitive, and behavioral symptoms were analyzed. Descriptive statistics and Bonferroni p-value correction for pairwise comparison were calculated. Results: 7, 311 manifest HD participants were included (612 YO, 5, 776 TO, and 923 LO). The average decline in TFC score from baseline to second visit (1.5–2.5 years) was significantly faster for YO (–1.75 points) compared to TO (–1.23 points, p = 0.0105) or LO (–0.97 points, p = 0.0017). Motor deficits were worse for LO participants at early stages of HD, and worse for YO participants at advanced stages. YO and TO participants had greater burden of behavioral symptoms at early stages of disease compared to LO. Discussion: YO is predictive of a faster functional decline for adults with HD when compared to those with TO and LO. Motor and behavioral manifestations differ based on age of onset. Highlights: This study compares HD manifestations while controlling for disease severity, detailing robust phenotypic differences by age of onset alone. These findings have implications for the clinical management of HD symptoms and have the possibility to improve prognostic and treatment precision.